A tree grows in Brooklyn - Smith, Betty 1896-1972 (HarperPerennial, 2005)
Young Francie Nolan, having inherited both her father's romantic and her mother's practical nature, struggles to survive and thrive growing up in the slums of Brooklyn in the early twentieth century.